Presence of circulating tumor cells in high-risk early breast cancer during follow-up and prognosis - Trapp, Elisabeth; Schneeweiss, Andreas (Journal of the National Cancer Institute, 2019)
AbstractBackground. The prognostic relevance of circulating tumor cells (CTCs) at the time of primary diagnosis has been well established. However, little info